Faktor-Faktor Yang Berhubungan Dengan Kinerja Petugas Kesehatan Di Puskesmas Gandus Palembang Tahun 2017 - Mutmainah, Siti; Amar Muntaha; Indra Martiandra (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Every person who solely aims to improve the healthiness can be considered as the human resources in aspect of Health. All the human resources, which take part in that aspect, carry the performance in one organization, both for the Head and the workers. This study is conducted in order to know the factors that are related to the performance of the health workers at Puskesmas Gandus Palembang 2017. The method of this study is analytical with research design cross sectional. The total of the samples are 35 respondents. Questionnaire is used in the data collection, as this study is a quantitative research. The Univariate, Bivariate, and Multivariate with logistic regression method is used to analyze the data. The result of the analysis by using Univariate shows that the variables of good work experience is about 45.7%, appropriate education 25.7%, teamwork 34.3%, appreciation 57,1%, and good instruction 27.7%. Analysis of Bivariate shows that the variables of work experience, education, and teamwork are not related to the performance. The variable of appreciation have a relation with the performance by having P value of 0.006 and OR value of 9.750, and the variable of instruction have also a relation with the performance by having P-value of 0.011 and OR value of 9.500. Multivariate analysis shows that the variable that is significant and strongly affects the performance is the variable of Appreciation (P ? value = 0.006, OR = 9.750). In conclusion, it is known that Appreciation is the most dominant variable that affects the performance of the Health Workers at PuskesmasGandus Palembang. It is suggested that the Head of the Puskesmas should give more appreciation and instruction so that it can increase the performance of the Health workers there.